Observance of Cialdini’s Principles of Speech Act of Persuasion in 2016 us Presidential Debates - Arisetiyani, Yenika; Yuliasry, Issy (Universitas Negeri Semarang, 2017)
Persuasion is an important factor to politicians to show the power and influence the people. In the United States Presidential Election, debate is one of the tools to convey the candidates' message. Most of the utterances used in debates aimed at affecting and convincing the audiences or the voters. Persuasion according to Searle (1979) is regarded as a directive speech act in which the speaker’s intention is to make the hearers to commit him or herself to perform some form of action. Most of the researchers conducted persuasive speech acts from the point of view of discourse. There is no study about natural data like debates. This study is a study about observance of Cialdini’s principles of speech acts of persuasion in 2016 US presidential debates. Therefore, there are six principles that must be observed, namely consistency, authority, reciprocity, social-evidence, preference/ liking and rareness/ scarcity. It used descriptive qualitative method to get the findings. The findings of the study are proved that most of the presidential candidates observed Cialdini’s principles. They used several ways like asking the voter’s need, making a promise, and disfiguring the interlocutors. Finally, this thesis provides suggestion regarding to the findings. At this point, the first plan is to present some tested principles of persuasion in debate classes. Next point is how you might use the principles to increase community interest in your topic, and to win people over, fairly and ethically, to the way of thinking.